2021
DOI: 10.32744/pse.2021.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Teachers 'and students' ideas about the existing advantages and possible risks of using digital products in the educational environment

Abstract: An integral feature and an urgent task of the modern education system is the use of digital products in educational practice. The forced implementation of mass distance learning in the period 2020-21 showed both the advantages and disadvantages of digital learning and set new horizons for optimizing this process. In May-June 2021, a study consisting of two parts was conducted: 1) an online survey of teachers of the general education system in order to determine the ideas about the advantages and risks for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…The educational infrastructure based on using the potential of digital environment aims at active inculcation of modern learning technologies in the educational process involving continuous monitoring and quality control of mathematics and computer science teaching -with the purpose to objectively evaluate the extent of learning materials acquisition and their influence on the results required for completing the curriculum, in order to timely update the subject content and organise corrective procedures towards improving the quality of assimilation of the basic knowledge. Fundamentalisation of education makes it possible to structure the educational process in such a way that students can develop new knowledge and skills independently on the grounds of basic, solid and systemic knowledge [23]. Fundamentalisation of education is realised through continuous self-education.…”
Section: Resultsmentioning
confidence: 99%
“…The educational infrastructure based on using the potential of digital environment aims at active inculcation of modern learning technologies in the educational process involving continuous monitoring and quality control of mathematics and computer science teaching -with the purpose to objectively evaluate the extent of learning materials acquisition and their influence on the results required for completing the curriculum, in order to timely update the subject content and organise corrective procedures towards improving the quality of assimilation of the basic knowledge. Fundamentalisation of education makes it possible to structure the educational process in such a way that students can develop new knowledge and skills independently on the grounds of basic, solid and systemic knowledge [23]. Fundamentalisation of education is realised through continuous self-education.…”
Section: Resultsmentioning
confidence: 99%
“…With all the obviousness of the need to use digital products and technologies in education, it should be noted that the subjects of the educational process (teachers and students) can understand the goals and forms of their use in different ways (Puchkova et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The transition to online learning and online practices during the COVID-19 pandemic has affected teachers' work, learning, well-being, and resilience. Research has found that 80% of teachers and 98% of students highly appreciate the need to use digital products in educational practice (Puchkova et al, 2021). A digital educational product is an educational product (text documents, photographs, video clips, and other educational materials) presented in electronic digital form and includes structure, subject content, and metadata about it.…”
Section: Introductionmentioning
confidence: 99%